An Updated Typology of Written Corrective Feedback: Resolving Terminology Issues - Bonilla López, Marisela (2021)
The extensive amount of literature on written corrective feedback has dispelled many doubts that question its effectiveness. However, despite this valid contribution, there is still controversy about pedagogical recommendations found in such literature, particularly, after conducting a systematic bibliographic review. The results reveal an overall lacks consistency, to the extent that a detailed classification based on both scope and type is not feasible. The objective of this article, thus, is to address previously gleaned issues by elucidating the two most problematic variables found in such literature in order propose an updated typology of written CF.